Kajian Hubungan Antara Perubahan Tutupan Lahan Dan Dinamika Kelimpahan Jenis Gajah Sumatera (Elephas Maximus Sumatranus Temminck, 1847) Di Taman Wisata Alam Seblat Tahun 2011-2020 - Suyanti, Erni; Susatya, Agus; Wiryono; Brata, Bieng; Suhartoyo, Hery (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2024)
Seblat Natural Tourism Park is substantial for the well being of Sumatran Elephant which provides suitable habitat in Bengkulu Province. The conversion of former production forest area with Particular Function of Elephant Training Center of Seblat into Convertible Production Forest Area of Seblat as wide as 710 hectares in 2011, and forest enroachment activities resulted in fragmentation of Sumatran Elephant habitat. This fragmentation led to the isolation of Seblat Natural Tourism Park and separation from surrounding forest area, which affects the species abundance of Sumatran Elephant. A study is required to understand the relationship between land cover change and dynamics of species abundance of Sumatran elephant during the period of 2011-2020. The study was conducted in the TWA Seblat with the area of ​​±7,768.36 hectares. Data used in this study were secondary data, particularly inventory data of Sumatran Elephants from the BKSDABengkulu which was obtained using the path transect method from patrol activities as many as ±228 patrols for ±1596 days, and land cover data which was obtained from the Directorate of Forest Resources Inventory and Monitoring, Directorate General of PKTL. Spatial analysis was carried out by performing topology test using ArcGIS 10.4 software and land cover classification based on SNI 7645:2010. Topology test resulted in 1 forest cover class and 6 non-forest cover classes. Statistical analysis carried out was multiple linear regression using the IBM SPSS 26 application by performing the Anova test or F test, and T test. The results of multiple linear regression analysis showed the correlation value (R) 0.753 indicated that there was close relationship between secondary dryland forest (X1) and shrubs (X2) with the dynamics of the species abundance of Sumatran elephant (Y). The contribution of variable X1 and variable X2 in influencing variable Y was56.7%, and 43.3% was influenced by other variables which unincluded in this study. The calculated F value is 3.935 with p value 0.081, andbecause the p value is higher than 0.05, simultaneously secondary dryland forest (X1)  and shrubs (X2) did not influence the dynamics of the species abundance of Sumatran elephant (Y). The calculated T value is 1.776 with value of p=0.126, because value of p is higher than 0.05, partially there is no significant influence between secondary dryland forest (X1) on the dynamics of the species abundance of Sumatran elephant species (Y). Determining the influence of shrubs (X2) on the dynamics of the species abundance of Sumatran elephant (Y) resulted in T value of 2.579 and value of p=0.042, with value of p is lower than 0.05 means that there were significant effect between the two variables.